Chair of Mayor of Corporation - Ghosh, Ayan (2023)
Chair of the mayor with BMC coat-of-arms. Though the mayor is the first citizen of Mumbai, the position is ceremonial. Executive power is actually wielded by an IAS officer who serves as municipal commissioner. Elections are held every five years and elected corporators are responsible for the basic civic infrastructure and enforcement of tax collection.